The ecology, productivity and economic of swiftlet (Aerodramus fuciphagus) farming in Kota Bangun, East Kalimantan, Indonesia - Mursidah MURSIDAH; Abubakar M. Lahjie; MASJAYA MASJAYA; Yaya Rayadin; YOSEP RUSLIM (Society for Indonesian Biodiversity, 2020)
Abstract. Mursidah, Lahjie AM, Masjaya, Rayadin Y, Ruslim Y. 2020. The ecology, productivity and economic of swiftlet (Aerodramus fuciphagus) farming in Kota Bangun, East Kalimantan, Indonesia. Biodiversitas 21: 3117-3126. Swiftlet nest is a high-value non-timber forest product produced from the saliva of swiftlet birds. While the demands for this commodity continue to increase in global market, careless harvesting techniques have diminished the swiftlet population and the production of swiftlet nests, threatening its sustainability. One effort to solve this problem is by developing swiftlet farming which involves building swiftlet. This research aimed to analyze the ecology, productivity, and financial feasibility of swiftlet farming of different-sized swiftlet houses in Kota Bangun Subdistrict, East Kalimantan, Indonesia. This research used qualitative and quantitative analysis methods. Data were collected using purposive sampling to determine the location, sample of swiftlet houses, and interviews with respondents. Quantitative analysis on the financial performance of swiftlet farming was analyzed using the net Benefit-Cost Ratio (net B/C), Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PP) methods. The results showed that swiftlet nest production in Kota Bangun begins in the third year and ends between 27 and 45 years later, depending on the age and size of the house as well as the quality of the timber. The swiftlet house with a size of ??512 m2 had the net B/C of 4.06, NPV of IDR 1,403.79 million, IRR of 30%, and PP of 5.44 years. The swiftlet house with a size of ??1,600 m2 had the net B/C of 2.27, NPV of IDR 1,774.83 million, IRR of 24.09%, and PP of 9.4 years. Our study suggests that swiftlet farming is financially highly feasible, especially for the swiftlet house with a size of 512 m2.